L’art sami - García-Antón, Katya; Gullickson, Charis; Ljøgodt, Knut; Persen, Synnøve (Perspective, 2019)
Depuis quelques années, les artistes samis font l’objet d’une attention croissante, que ce soit en Scandinavie ou à l’échelle internationale, et ils ont porté l’art sami sur le devant de la scène artistique contemporaine. Nous pourrions ainsi citer la récente participation de certains d’entre eux à la documenta 14 (Cassel Athènes, 2017), ou des expositions comme Sámi Stories (New York Anchorage, 2014-2015), Let the River Flow (Oslo Stockholm, 2018-2019), ou encore l’actuelle Histories: . In recent years Sami artists have received increasing attention, both in Scandinavia and internationally, and have brought sami art to the contemporary art scene. We could mention the recent participation of some of them in documenta 14 (Cassel; Athens, 2017), or exhibitions such as Sámi Stories (New York; Anchorage, 2014-2015), Let the River Flow (Oslo; Stockholm, 2018-2019), or current history: .